Evaluation of a System to Assess Herbicide Movement in Straw under Dry and Wet Conditions - Thais dos Santos, Izabela [UNESP]; Ferraz Santos de Brito, Ivana Paula [UNESP]; Alves de Matos, Ana Karollyna [UNESP]; Pinheiro de Miranda, Valesca [UNESP]; Meirelles, Guilherme Constantino [UNESP]; Oliveira de Abreu, Priscila [UNESP]; Alcántara-de la Cruz, Ricardo [UNESP]; Velini, Edivaldo D. [UNESP]; Carbonari, Caio A. [UNESP] (MDPI, 2024)
Straw from no-till cropping systems, in addition to increasing the soil organic matter content, may also impede the movement of applied herbicides into the soil and, thus, alter the behavior and fate of these compounds in the environment. Rain or irrigation before or after an herbicide treatment can either help or hinder its movement through the straw, influencing weed control. Our objective was to develop a system for herbicide application and rain simulation, enabling the evaluation of the movement of various herbicides either in dry or wet straw under different rainfall volumes (25, 50, 75, and 100 mm). The amount of the applied herbicides that moved through the straw were collected and measured using a liquid chromatograph with a tandem mass spectrometry system (LC-MS/MS). Measurements obtained with the developed system showed a high herbicide treatment uniformity across all replications. The movement of the active ingredients through the straw showed variability that was a function of the applied herbicide, ranging from 17% to 99%. In wet straw, the collected herbicide remained constant from 50 to 100 mm of simulated rainfall. For the wet straw, the decreasing percentages of the herbicide movement through straw to the soil were sulfentrazone (99%), atrazine and diuron (91% each), hexazinone (84%), fomesafen (80.4%), indaziflam (79%), glyphosate (63%), haloxyfop-p-methyl (45%), and S-metolachlor (27%). On the dry straw, the decreasing percentages of the herbicide movement were fomesafen (88%), sulfentrazone (74%), atrazine (69.4%), hexazinone (69%), diuron (68.4%), glyphosate (48%), indaziflam (34.4%), S-metolachlor (22%), and haloxyfop-p-methyl (18%). Overall, herbicide movement was higher in wet straw (with a previous 25 mm simulated rainfall layer) than in dry straw. Some herbicides, like haloxyfop-p-methyl and indaziflam, exhibited over 50% higher movement in wet straw than dry straw after 100 mm of simulated rain. The developed system can be adapted for various uses, serving as a valuable tool to evaluate the behavior of hazardous substances in different agricultural and environmental scenarios.
Keywords: herbicide leaching; LC-MS/MS analysis; non-tillage; simulated rain; straw retention